Pengaruh Intensitas Penggunaan Smartphone Terhadap Regulasi Emosi Pada Mahasiswa - Siti Julia Sari; Adhani Dhea Saputri; Meilysa Anggraini; Sri Retina; Aulia Puspita Sari (CV. Doki Course and Training, 2024)
The intensity of smartphone use among students is increasing rapidly, making students feel afraid of being left behind if they don't use it. The intensity of using smartphones can have an impact on emotional regulation in students. With unstable emotional changes, students need the ability to regulate emotions. Aldao, Sheppes, & Gross, (2015) state that emotion regulation strategies are very important for making adjustments. In this case, students must make adjustments from using smartphones. In this situation, the ability of emotion regulation strategies In this situation, the ability of emotion regulation strategies can help students overcome the problems they face (Wilson, Barnes-Holmes, & Barnes-Holmes, 2014). This study aims to determine the effect of intensity of smartphone use on emotional regulation in students using quantitative containing scale items Intensity of smartphone use (MPIQ Scale), Self-regulation (YAPS), Self-regulation (ERQ), data analysis used in this study is Pearson Correlation with the help of JASP. This research uses a quantitative approach, survey method. The results showed that the intensity of smartphone use has a direct positive effect on emotional regulation in students. Self-regulation has a direct positive effect on emotions in students. Self-regulation has a positive directeffect on emotion regulation in college students. The results showed that the intensity of smartphone use has a direct positive effect on emotional regulation in students. Self-regulation has a direct positive effect on emotions in college students. Self-regulation has a direct positive effect on the intensity of smartphone use.